Genome analysis of protozoan parasites. Proceedings of a workshop - Morzaria, S.P. (International Laboratory for Research on Animal Diseases, 1993)
This workshop proceeding reviews the current state of some of the major genome programs in the world, reviews recent developments in the genome analysis of the important protozoan parasites such as leishmania, toxoplasma, trypanosoma and theileria; reviews major technological advancements contributing towards eukaryotic genome analysis; identifies major applications of the knowledge gained from the genome analysis projects; identifies ILRAD's (International Laboratory for Research on Animal Diseases) needs for theileria and trypanosoma genome analysis, and explores possibilities of collaboration with an international group of scientists involved in genome analysis projects. Topics of discussion include molecular dissection of genomes, establishing a laboratory for parasite genome analysis, genetic analysis of theileria and plasmodium, genetic analysis of trypanosomes and techniques for physical and functional analysis.